IT policy and information security management based on ISO 27001 - Ramos Mamami, Roy Guiller (2023)
Technology in recent times has been changing by leaps and bounds and it is natural to acclimatize to these technological changes and even more so due to the covid-19 pandemic in the world, causing drastic change in company strategies. The article presented below aims to describe the causes and effects of the ISO 27000 standard, focusing on the ISO 27001 standard. In this sense, to ensure an adequate information security policy that, in the absence of national legislation on the subject, must be based on international standards, comparative law and autonomy of will. The methodology used to explain the various areas of impact is followed by the ISO 27001 standard in the domain that refers to compliance and which includes: The ISO 27001 standard helps companies comply with legal requirements, which have the purpose of avoiding the violation of the legislation or the breach of any legal obligation of the entities of any security requirement.